2002
DOI: 10.1002/jrs.809
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of micro‐stress and phase transition in sol–gel‐derived multideposited coatings of barium titanate using Raman spectroscopy

Abstract: Thin films of barium titanate (BaTiO 3 ; BT) of various thicknesses (20, 60, 120, 160 and 200 nm) were deposited by a modified sol-gel route on M-plane sapphire [Al 2 O 3 : (1010)] substrates. Raman spectroscopy (RS) and x-ray diffraction (XRD) were used to evaluate the stress and structural changes with respect to film thickness and establish a correlation. Raman bands and x-ray peak intensities of 20 nm thick films were too weak to reveal any structural information. Structurally, all other films showed a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The explanation of the broadened peak can be also the greater damping effects in thin films (Fig. 5) compared to the bulk case [42] what is in agreement with the experimental data [17,41]. The peak becomes narrower and higher with increasing film thickness or when ss J approaches the value of b J (Fig.…”
Section: Numerical Results and Discussionsupporting
confidence: 89%
“…The explanation of the broadened peak can be also the greater damping effects in thin films (Fig. 5) compared to the bulk case [42] what is in agreement with the experimental data [17,41]. The peak becomes narrower and higher with increasing film thickness or when ss J approaches the value of b J (Fig.…”
Section: Numerical Results and Discussionsupporting
confidence: 89%
“…For such compound, the E(2TO) ͑ϳ307 cm −1 ͒ phonon mode indicates an asymmetry within the TiO 6 octahedra, which suggest the presence of a tetragonal crystalline structure. 18 This figure also revealed that the E(2TO) mode become weaker with the increase of the Zr content. Such behavior indicate that the substitution of Ti by Zr in the BaTiO 3 structure results in structural disorder and, consequently, in structural phase transition.…”
Section: Resultsmentioning
confidence: 69%
“…Thin films of barium titanate using X-ray diffraction 13 and Raman spectroscopy 13,14 have been studied to investigate the ferroelectric-paraelectric transition. Recently, ferroelectric transition in barium titanate nanoparticles has been studied using NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…21 In order to investigate the temperature and pressure dependence of the dielectric constant (dielectric susceptibility) and the spontaneous polarization close to the phase transitions in BaTiO 3 , the Landau mean field models have been employed. 12,13,15 By expanding the free energy in terms of the order parameter (spontaneous polarization PÞ, the temperature dependence of the P and the dielectric susceptibility (dielectric constant Þ can be obtained by determining the coefficients in the free energy expansion. The temperature dependence of the bilinear coupling constant (order parameter) of the soft-optic and acoustic mode in hexagonal barium titanate has been analyzed using the experimental data 12 according to the prediction of the mean field theory.…”
mentioning
confidence: 99%